Learning to succeed : a radial look at education today and a strategy for the future - Paul Hamlyn Foundation; National commission on education (London : Heinemann, 1993)
A review from the National Commission on Education which poses key questions on education and training in the UK, and attempts to answer them in straightforward language. The report is concerned with identifying coming needs and how they can be met over the next 25 years.
Includes indexes.
Keywords: Education